Reformas educacionais e gestão democrática no estado do Acre: repercussões no trabalho do núcleo gestor da escola - Lucia de Fatima Melo (2010)
This thesis has searched to understand the work carried out by the Managing Center of the Basic Education in Acre's public schools, regarding the reforms in the two last decades in Brazil, and the outcomes in the so-called democratic management of schools. The investigation was set from two initial observations. The first is that, a new set of rules in the incipient democratic school management established by the current national legislation, has been diminished by the managerial staff of education, envisioning its modernization, proposing an efficient and effective management, transferring to the civil society part of its costs related to such activities. The second is that the educational reforms on the way have meaningfully altered the school context in its organization and management, demanding a new reorganization of the activities for the current professionals in the public school system working in the basic educational setting, which has resulted in a restructuring of the pedagogical work. The study has evidenced the transformations which occurred in the school management and organization in Acre, specifically from 1995 onwards. In the scope of these new movements was that new governance was proposed to the schools originating the managing center which was composed by the school principal, the teaching coordinator, and the administrative coordinator, who constituted the subjects of this research. The objective of this investigation was to analyze the repercussions happening in the daily work of these subjects during this process, examining the nature, meaning, and transformations in the school organizational structure, creating a knowledge base of the profile, perceptions, satisfaction level, contradictory situations, and resistance strategies. The investigation configured itself as a descriptive survey, supported by bibliographic and documental research, having as main data collecting tools the quantitative and qualitative elements (questionnaire). The study has also shown convergences and divergences touching the educational reforms and policies regarding the school management in Acre. It was possible to notice from the study that the managing center manifests its satisfaction related to the various aspects in the educational reform, what does not prevent starting the resistance actions in their daily life, opposing the work intensification, which presents itself in a complex and diffuse manner, not always noticed. In this process, the managing center gathers strength which produces emancipating possibilities that if once empowered, they can contribute to a wider struggle of the teachers and school working staff in general.